2012
DOI: 10.5539/jas.v4n2p139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Influencing Factors of Technology Adoption of Different Land Based Enterprises of Farmers under Diversified Farming System

Abstract: The present study to assess the technology adoption behaviour of farmers of different land based enterprises under diversified farming system was conducted in Sonitpur district of Assam, India. A sample size of 135 farmer respondents was drawn from three Agricultural Sub-Divisions of the district by using proportionate random sampling technique. The study shows that among the socio-economic variables under study, except age, other variables namely; education, extension contact and annual income were found havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 1 publication
3
12
1
1
Order By: Relevance
“…The same thing was stated by Moga, Constantin, and Antohi (2012) elderly could lead to a negative attitude towards the use of Information and Communication Technology in Romania. However, contrary to research Xu and Wang (2012), Lestrelin et al (2011) andSingha, Baruah, Bordoloi, Dutta, andSaikia (2012) showed the adoption did not depend on the variable age of farmers.…”
Section: Agecontrasting
confidence: 39%
See 1 more Smart Citation
“…The same thing was stated by Moga, Constantin, and Antohi (2012) elderly could lead to a negative attitude towards the use of Information and Communication Technology in Romania. However, contrary to research Xu and Wang (2012), Lestrelin et al (2011) andSingha, Baruah, Bordoloi, Dutta, andSaikia (2012) showed the adoption did not depend on the variable age of farmers.…”
Section: Agecontrasting
confidence: 39%
“…Research Singha et al (2012) at Sonitpur Assam District, India, showed that www.ccsenet.org/jas Journal of Agricultural Science Vol. 5, No.…”
mentioning
confidence: 99%
“…In addition to resilience, microenterprises increased output at a quicker rate when they had individuals with agronomic experience. This finding complimented Singha et al (2012) claims that entrepreneurs versed in biological systems had better long-term success with their organic fertilizer ventures.…”
Section: Discussionsupporting
confidence: 68%
“…An employee who is knowledgeable about decomposition processes can communicate this information to fellow coworkers (Hinrichs et al, 2009). Singha et al (2012) emphasizes that coworkers with experience in agriculture or its related industries tend to have more knowledge about biological systems, offering a foundation for understanding decomposition processes. In addition, those outside the agricultural sector can stimulate conversation about new ideas and strategies to streamline operations (Oleas et al, 2009).…”
Section: Labor/education Related To Processingmentioning
confidence: 99%
“…Farm qualities, such as size, type of production; the characteristics of the farmer or firm that runs the farm, such as age, technical knowledge, education; the business economic profile, such as the firm's size and financial strength; environmental aspects, such as crop pests and diseases; in addition to access to insurance, subsidies, markets, technical assistance may all affect the farmers diversification level (Pope & Prescott, 1980;Bosma, Udo, Verreth, Visser, & Nam, 2005;Mcnamara & Weiss, 2005;Bravo-Ureta, Cocchi, & Solís, 2006;Singha, Baruah, Bordoloi, Dutta, & Saikia, 2012;Longpichai, 2013;Ruf & Schroth, 2015).…”
Section: Introductionmentioning
confidence: 99%